Thermal Efficiency of Water Tube Boiler Reviewed from the Effect of Air Fuel Ratio and Water Level Control on Superheated Steam Production - Salsabila, Salsabila; Zurohaina, Zurohaina; Tahdid, Tahdid (Faculty of Mathtmatics and Natural Sciences, 2024)
The Cross Section Double Drum Water Tube Boiler is a closed vessel designed to produce steam. This boiler has two main components: the combustion chamber, which serves as the place for fuel combustion, and the steam drum, where the phase change occurs, turning water into steam. The Cross Section Double Drum Water Tube is characterized by tubes arranged transversely to the drum with a 65 incline, aiming to expand the heat transfer area. This study was conducted to determine the effect of the air-to-fuel ratio (17, 19, 21, 23, 25) and water level (20%, 30%, 40%, 50%, 60%) on thermal efficiency. The fuel used in this study is LPG gas. From the results obtained, the optimal air-to-fuel ratio was found to be 23 with a water level of 50%, achieving a thermal efficiency of 72.39% at a temperature of 205C and a pressure of 9.3 bar. Based on the research conducted, it was concluded that the air-to-fuel ratio and water level significantly affect the boiler's efficiency.